Implementação de um emulador de rede para testes de suportabilidade a afundamentos de tensão para inversores conectados à rede elétrica - Pissaia, Guilherme Gemi (2023)
The present work presents the step by step of the design of electronic instrumentation circuits, elaboration of the design of printed circuit boards and the method used to create scripts in python programming language, all this aimed at the use of a multilevel cascade converter intended to be used for voltage sag tests in wind generators. For this, an introduction to the structure of the converter itself is given, as well as the study of the network codes of some countries, including Brazil, to understand why this work is being done and what are the connection requirements for each location. Naturally, all the instrumentation and coding done was designed encompassing various situations, from the most diverse connection requirements to the different types of short circuit that can occur in an electrical system. Therefore, the programs were structured in order to simulate faults for short-circuit types A, B, C and E, with different magnitudes and lag angles. The study of the different calculation modes for each type of short circuit is also briefly discussed, in order to understand what was done in the scripts.